Recent developments on cylindrical contact force models with realistic properties - Isaac, Fernando (2016)
In this work a numerical study was performed involving a spatial revolute joint formed by a journal and a bearing with the purpose to evaluate the effect of the bearing thickness, misalignment and impact velocity on the force generated in the contact process. These analyses were run in a developed three-dimensional finite element model that simulates the referred aspects in a realistic way. This numerical tool allows defining both radial and axial clearances, which are important aspects in the analysis of operating conditions of actual journal-bearing joints. Resulting forces and stress profiles were calculated in different regions of the model, contributing to the accurate definition of design parameters. The generated data was ultimately compared and validated with the one obtained from the models that are currently used in the context of multibody dynamics and predict kinematic aspects of mechanical systems involving cylindrical contact interaction.